THEORETICAL AND LEGAL BASIS OF THE INCOMES OF THE CIVIL SOCIETY INSTITUTIONS IN UKRAINE - Ткачук, Ірина (Socio-economic relations in the digital society, 2019)
The actuality of the research is related to the existence of a request by non-governmental organizations to formulate a model of organization and management of civil society finances in general and a model of financial support for the activities and development of non-governmental organizations in Ukraine in particular. The purpose of the article is to carry out a study of the legal and theoretical foundations of the incomes of the civil society institutions in Ukraine. The article presents the author’s understanding of the category «financial resources of civil society institutions». According to it, «Financial resources of civil society institutions» are monetary funds at the disposal of civil society institutions that have a legal source of origin and are aimed at achieving of the statutory goals of these institutions. The article highlights the main legal acts of Ukraine, which regulate the activity of non-governmental organizations in Ukraine, and give them the right to receive incomes from different sources. The peculiarities of legal regulation of financial support of various types of non-governmental organizations in Ukraine are highlighted. Scientific approaches to the classification of civil society institutions’ income have been investigated. Thus, the author’s approach of the classification of sources of financial support for the activities of non-governmental organizations in Ukraine has been formulated. Accordingly, all sources of income of NGOs are divided into 5 large groups: Own funds; Public funds; Charity proceeds; Income from business activities; Other receipts. This approach provides the basis for further theoretical and analytical studies of the financial support for: the activities and development of civil society organizations in Ukraine; for the study of the impact of its indicators on the effectiveness of NGOs activities in Ukraine and on the indicators of civil society development in Ukraine.